(untitled) (Journal of Environmental Microbiology and Toxicology, 2024)
Chromium toxicity, present at elevated levels, poses a challenge for its remediation. The use of agricultural spent biomass as an adsorbent is one of the best mitigation efforts to date. This study investigates the adsorption of hexavalent chromium ions (Cr(VI)) onto Sugarcane Bagasse–Lemongrass Blend, and employs nonlinear regression to evaluate several isothermal models. The performance of the models was assessed using multiple error functions. While most models showed good fits, the Koble-Carrigan, Henry, and Dubinin–Radushkevich models showed poor convergence or high error. The Multiobjective Optimization on the Basis of Ratio Analysis (MOORA) method was employed for model ranking, as the error function analysis yielded inconsistent results. MOORA indicated that the Toth, Freundlich, and Fritz–Schlunder III models were the top performers. The Toth model calculated the maximum adsorption capacity of qmT of 0.91 mg/g, which is slightly lower than the experimental maximum of 1.21 mg/g. The Toth exponent nT = 0.72 value is closer to unity, suggesting a relatively homogeneous surface with adsorption behavior that resembles the Langmuir model. Despite robust modeling, the limited dataset introduces uncertainty in parameter estimation, underscoring the need for larger datasets. This study also emphasizes MOORA’s potential in adsorption science as an efficient multi-criteria model selection tool.